Ice cream soup - Ingalls, Ann; Watson, Richard (Penguin Young Readers, an imprint of Penguin Group (USA) Inc. New York, New York, 2013)
"Look at what I can make. I can make an ice cream cake! One scoop, two scoops, ice cream goop. I think I made some ice cream soup!"--Page 4 of cover